APPLYING THE IMAGES CITY VALUE TO IMPROVE THE IDENTITY OF WUALAI’S LOWLAND COMMUNITY IN THAILAND - Umpiga Shummadtayar; Kazunori Hokao; Pawinee Iamtrakul (International Association of Lowland Technology, 2012)
Each of developing communities is interested in basic improvement and sustainable development plan as especially for ‘lowland environmental’, ‘community identity’ and ‘social value’. This paper clear to recognize and create value that impress people in community and visitor in which the space syntax theory that the urban area can be represented as a matrix of connected spaces. There were explained to the physical problems; the historical part and perception of a city image and improving the image of community identity, environment and social value. Particularly, the resident perception on damage of the city could be forming of image and creating social networks with life satisfaction or community living. Based on physical environment and network functional related to develop the design guideline, suitable model and policy framework. To concludes by reach to a greater understanding of city image and discovers how to quantify its importance for each particular case study in term of ‘identity’, ‘structure’ and ‘meaning’. Moreover, this information can support decision-makers to policies plan by prioritizing certain aspects depending on the sense of place by sample groups. These suitable model, though to the methodological proposal idea can be extrapolated to other cities, as a process for measuring city identity image.